Isolation of Flavones from The Anti--inflammatory Fraction of Orthosiphon Stamineus Extracts - , L, Vuanghao; A, Sadikun; M.Z, Asmawi (Malaysian Journal of Science, 2005)
Fraction Cf2b from the crude chloroform extract of Orthosiphon stamineus was found to be the most activee in inhibiting carrageenan induced hind paw oedema in mice. It suggested that the most active anti-inflammatory fraction of the extract was found in the fraction Cf2b. Two compounds have been isolated and identified from this active fraction; 5,3' -dihydroxy-6,7,4' -trimethoxyflavone 1 and 5,6,7,3',4' -pentamethoxyflavone 2. Compounds 1 and 2 are flavones which commonly known as eupatorin and sinensetin respectively. Both compounds were identified and elucidated through spectroscopic methods. Eupatorin is the major compound and sinensetin is the second major compound present in the active fraction.